Approximal Caries Detection by DIFOTI: In Vitro Comparison of Diagnostic Accuracy/Efficacy with Film and Digital Radiography - Á. Ástvaldsdóttir; K. Åhlund; W. P. Holbrook; B. de Verdier; S. Tranæus (International Journal of Dentistry)
The aim of the present study was to compare the diagnostic accuracy/efficacy of digital imaging fiber-optic transillumination (DIFOTI) with film and digital radiography, in detection of approximal caries lesions. One hundred and twelve approximal surfaces were scored for caries, using DIFOTI images film and digital radiographs. All three sets of images were examined twice by 8 observers, with a minimal interval of one week between examinations. Validation of histological sections served as a reference standard. Reproducibility, based on intra- and interobserver agreement, was similar for all three methods. At diagnostic threshold D1 (enamel and dentin caries), DIFOTI showed significantly higher sensitivity, but differences in specificity between methods were nonsignificant. Diagnostic accuracy in the form of area under the receiver operating characteristic curve (AUC) was significantly higher for DIFOTI. At diagnostic threshold D3 (dentin caries), the differences in sensitivity and AUC among methods were nonsignificant, but DIFOTI showed significantly lower specificity. Compared with the radiographs, DIFOTI showed closer agreement, expressed as weighted kappa values, with the reference standard. The results show that under in vitro conditions, the diagnostic accuracy of DIFOTI in detecting early approximal enamel lesions is greater than that of film and digital radiography, while the potential for detecting lesions in dentin is similar for all three methods.